Brief review on application of nonlinear dynamics in image encryption - Ozkaynak, Fatih (Springer, 2018)
Chaos-based cryptology has become one of the most common design techniques to design new encryption algorithms in the last two decades. However, many proposals have been observed to be weak against simple known attacks. However, security of proposals cannot be proved. An analysis roadmap is needed for the security analysis of new proposals. This study aims to address this shortcoming. Analysis and test results show that many chaos-based image encryption algorithms previously published in the nonlinear dynamics are actually not as secure as they are expressed although these algorithms do pass several statistical and randomness tests. A checklist has been proposed to solve these problems. The applications of the proposed checklist have been shown for different algorithms. The proposed checklist is thought to be a good starting point for researchers who are considering to work in chaos-based cryptography.
Keywords: Chaos; Cryptography; Cryptanalysis; Hyperchaos; Image cipher; DNA